Djetneut tells stories - Djetneut Kul'u (Alexander King, 1998)
1. Legend about lake near Khailino and an old man. 2. Story about red something? 3. Mountain legend. 4. Legend about a woman. 5. Notantola. 6. Cannibal - real story. 7. Tape started after beginning of story. 39:56 - end of a story. 40:00 - 43:20 – story. Last 3 mins blank (no recording on tape). Born near Khailino on tundra in Yaranga. Spoke limited Russian.